Hydroxyethyl Isoflavonoids from the Leaves of Maclura tricuspidata - Jo, Yang H.; Yeon, Sang Won; Ryu, Se Hwan; Lee, Solip; Kim, Seon Beom; Hwang, Bang Yeon; Lee, Mi Kyeong (Current Organic Chemistry, 2021)
Maclura tricuspidata, which belongs to the Moraceae family, is widely distributed in Asia, including Korea. All parts of this plant, such as roots, fruits, and leaves, are rich in diverse bioactive compounds, especially xanthones and isoflavonoids. Investigation of the leaves of M. tricuspidata through various chromatographic techniques yielded fourteen compounds, including five new compounds. The new compounds were determined to comprise an isoflavonoid structure with hydroxyethyl moiety and defined as hydroxyethylisoflavones A-E (10-14) on the basis of 1D and 2D NMR and MS data. These compounds efficiently inhibited α-glucosidase activity.
Keywords: isoflavonoid